Alltag und Lebensverhältnisse des Hochmeisters in der Marienburg in der ersten Hälfte des 15. Jahrhunderts - Herrmann, Christofer (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)
Everyday life and living conditions of the Grand Master in Marienburg (Malbork) in the first half of the 15th century On the basis of a wide range of sources (rules of the order, accounts, letters, deeds/notarial instruments, chronicles, envoy reports, minutes of the estates and town meetings), a wealth of information can be gleaned about the everyday and private life of the Grand Master at Marienburg Castle in the first half of the 15th century. The letter from the Grand Master’s personal physician is particularly fruitful, as it provides numerous references to the lifestyle of the head of the Order. This source is included as an edition in the appendix to the article. Overall, it can be stated that the usual daily routine of a Grand Master was essentially characterised by three components: - Religious acts that were spread throughout the course of the day (participation in masses and prayers of the hours, in particular the daily night orthros between 11 p.m. and 2 a.m.). - Eating and drinking (court meals at midday and in the evening, morning soup, collacia). - Political and administrative activities (consultations, negotiations, councils with the dignitaries, envoy receptions, meetings of cities and estates, etc.), mainly in the mornings and afternoons. In addition to these three main areas of daily activity, which were largely of a public-representative nature, there was also a private sphere in the life of the Grand Master. The time for relaxing or entertaining activities was very limited, but the sources give partial insights into this personal sphere (e.g. pets, music, studies, amusement).